Anterior mediastinal mass in children following chemotherapy for malignant disease: Thymic hyperplasia vs recurrence - (:unkn) unknown (W.B. Saunders Ltd, 2003)
Anterior mediastinal masses in children following chemotherapy for malignant disease often cause diagnostic problems. Differential diagnosis of thymic hyperplasia from recurrence frequently poses a challenge both for the radiologist and the physician. Thymic hyperplasia was seen in five patients, three with Hodgkin's disease, one with Burkitt's lymphoma and one with Wilms' tumour, after chemotherapy. In one patient, thymic hyperplasia was proven by biopsy and the other four were followed. None of the masses in the anterior mediastinum showed difference in size or shape during follow-up. We recommend that such patients should be evaluated cautiously before planning an invasive procedure. In patients who did not have an anterior mediastinal mass prior to chemotherapy, diagnosis of thymic hyperplasia should be stressed. © 2003 The College of Radiographers. Published by Elsevier Ltd. All rights reserved.
Keywords: Anterior mediastinal mass; Computed tomography; Thymic hyperplasia